Spatial Planning and Policy Study of Food Estate Development on Peatland in Pulang Pisau and Kapuas Districts, Kalimantan Tengah, Indonesia - Rakuasa, Heinrich; Latue, Philia Christi (Nusantara Journal of Behavioral and Social Science, 2023)
The development of food estates to support food security in Pulang Pisau District covering 10,000 ha and Kapuas District covering 20,000 ha continues to be implemented. The clearing of food estate land is complete, but the processing of peat agricultural land ready for planting, the construction of irrigation channels, and the preparation of human resources (HR) are targeted to be completed by mid-2021. The purpose of this paper is to examine food estate spatial planning and policies related to environmental impact analysis and propose a reliable food estate management strategy through the literature review method. The results of the analysis show that not all peatlands are suitable for agricultural land with the potential for fires, the failure of past peatland projects in the area due to poor management, the conversion of forest land will disrupt the hydrological cycle resulting in flooding and disrupting the orangutan ecosystem, and agriculture in this area does not show a sustainable ecological dimension. Land management strategies are proposed; irrigation infrastructure development, liming, improving human resource knowledge related to peatland agricultural management, management and supervision. Abstrak: Pengembangan food estate untuk mendukung ketahanan pangan di Kabupaten Pulang Pisau seluas 10.000 ha dan Kabupaten Kapuas seluas 20.000 ha terus dilaksanakan. Pembukaan lahan food estate sudah selesai, namun pengolahan lahan pertanian gambut siap tanam, pembangunan saluran irigasi, dan penyiapan sumber daya manusia (SDM) ditargetkan selesai pada pertengahan tahun 2021. Tujuan dari tulisan ini adalah untuk mengkaji perencanaan tata ruang food estate dan kebijakan terkait analisis dampak lingkungan serta mengusulkan strategi pengelolaan food estate yang handal melalui metode kajian literatur. Hasil analisis menunjukkan bahwa tidak semua lahan gambut cocok untuk lahan pertanian yang berpotensi kebakaran, kegagalan proyek lahan gambut di masa lalu di daerah tersebut karena pengelolaan yang buruk, konversi lahan hutan akan mengganggu siklus hidrologi yang berakibat pada banjir dan mengganggu ekosistem orangutan, dan pertanian di daerah ini tidak menunjukkan dimensi ekologi yang berkelanjutan. Strategi pengelolaan lahan yang diusulkan adalah pembangunan infrastruktur irigasi, pengapuran, peningkatan pengetahuan sumber daya manusia terkait pengelolaan pertanian lahan gambut, manajemen dan pengawasan.